Students' perceptions, educational challenges and hope during the COVID‐19 pandemic. (12th August 2022) - Bryce, Crystal I.; Fraser, Ashley M.
Abstract: Introduction: The COVID‐19 pandemic has disrupted the lives of US students both at home and at school. Little is known regarding how adolescents perceive COVID‐19 has impacted (both positively and negatively) their academic and social lives and how protective factors, such as hope, may assist with resilience. Importantly, not all pandemic experiences are necessarily negative, and positive perceptions, as well as potential protective factors, are key to understanding the pandemic's role in students' lives. Method: Utilizing quantitative and qualitative approaches, the present study descriptively examined 726 6th through 12th grade (51% female, 53% White) students' perceptions of how COVID‐19 related to educational and life disruptions, and positive aspects of their lives, within the United States. Analyses additionally explored the role of pre‐pandemic hope in improving feelings of school connectedness during the pandemic. Results: Results showed that most students felt that switching to online learning had been difficult and their education had suffered at least moderately, with a sizeable proportion of students feeling less academic motivation compared with last year. When asked to share qualitative answers regarding perceived challenges and positive aspects of life, themes were consistent with quantitative perceptions. Students' pre‐pandemic hope positively predicted students' feelings of school connectedness. Conclusions: Findings paint a complex picture of youth's COVID‐19 experiences and have implications for proactive ways to support students as COVID‐19 continues to affect daily life and educational structures and practices.